KAJIAN DISTRIBUSI BAHAN KERING PADA 10 KLON UNGGUL UBI KAYU (Manihot esculenta Crantz) UNTUK DETEKSI SIFAT FISIOLOGI DI KEBUN PERCOBAAN TAMAN BOGO, PURBOLINGGO, LAMPUNG TIMUR - Siska Puji Lestari; Kukuh Setiawan; Muhammad Syamsoel Hadi; Setyo Dwi Utomo (JURNAL AGROTROPIKA, 2026)
The objective of this study was to determine the distribution pattern of dry matter from leaves to tubers in 10 cassava clones in two different land conditions (optimal and marginal). The experiment was arranged in a factorial randomized completely block design (RCBD) (2x10), with three replications, resulting in 60 experimental units. The variables observed included plant height, stem diameter, number of green leaves, fresh and dry weight of leaves, stems, and tubers. The results of the study indicate that differences in soil conditions and clones influence the distribution pattern of dry matter in cassava plants. The Garuda, UJ3, Sekoci, Soponyono, D9, and Vamas-1 clones exhibited relatively good growth and yield under both soil conditions, while Cino and Waxy performed better on optimal soil, and UJ5 showed good tuber formation only during the early growth stage. The most efficient dry matter distribution was shown by the Garuda and UJ3 clones, which produced the highest tuber weight at 10 months after planting (MAP), followed by Sekoci, Soponyono, D9, and Vamas-1, which were also able to accumulate high amounts of tuber dry matter. Conversely, the KM clone exhibited the lowest dry matter distribution, characterized by the lowest fresh and dry tuber weights under both soil conditions.